2022
DOI: 10.1038/s41420-022-01177-0
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circPGD contributes to gastric cancer progression via the sponging miR-16-5p/ABL2 axis and encodes a novel PGD-219aa protein

Abstract: CircRNAs have critical effects on tumor development and progression. However, circPGD effect on gastric cancer (GC) is still elusive. Nuclear and cytoplasmic RNA fractionation, and RNA-FISH assay examined the localization of circPGD in MGC-803 cells. qRT-PCR was conducted to detect the expression and prognostic significance of circPGD, miR-16-5p, and ABL2 within GC tissues. Meanwhile, qRT-PCR, luciferase reporter assays, rescue, and western blotting assays confirmed the interactions between circPGD, miR-16-5p,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…al showed that circUBA1 advances the development and metastasis of gastric tumor cells by sponging miR-375 [ 45 ]. Previous researchers have discovered that both hsa_circ0000885 and circPGD can promote cancer progression via sponging miR-16-5p [ 46 , 47 ]. Consistently, in our study, we found that circRANGAP1 promotes HCC progression by sponging miR-27b-3p.…”
Section: Discussionmentioning
confidence: 99%
“…al showed that circUBA1 advances the development and metastasis of gastric tumor cells by sponging miR-375 [ 45 ]. Previous researchers have discovered that both hsa_circ0000885 and circPGD can promote cancer progression via sponging miR-16-5p [ 46 , 47 ]. Consistently, in our study, we found that circRANGAP1 promotes HCC progression by sponging miR-27b-3p.…”
Section: Discussionmentioning
confidence: 99%
“…66 In contrast, Liu's team found that high expression of circPGD in gastric cancer tissues promoted EMT and inhibited the apoptosis of gastric cancer cells. Moreover, circPGD has been shown to exert biological effects not only by sponging miR-16-5p but also by encoding a novel protein, PGD-219aa, which promotes gastric cancer progression by acting on the SMAD2/3 and YAP signalling pathways 67 (Figure 3C).…”
Section: Circrna-encoded Proteins Regulate Tumour Cell Metastasis By ...mentioning
confidence: 99%
“…This study was approved by the Medical Ethics Committee of Jiangsu University, and all participants signed an informed consent form. HGC-27 were cultured according to the methods described in a previous article [22] .…”
Section: Patients and Specimensmentioning
confidence: 99%